Acute kidney injury after aminoglycoside exposure in two cystic fibrosis patients receiving triple CFTR modulator therapy - Deslais Martin; Novel-Catin Etienne; Nove-Josserand Raphaële; Fouque Denis; Durieu Isabelle (Journal of Nephrology, 2026)
Abstract The discovery of Cystic Fibrosis Transmembrane conductance Regulator (CFTR) modulators has revolutionized the management and clinical outcomes of cystic fibrosis. However, the pleiotropic effects of these new treatments outside the lungs are still largely unknown. Here we report two unusual cases of acute kidney injury in patient with cystic fibrosis (pwCF) following a first exposure to aminoglycoside while under triple correction therapy. We hypothesize that CFTR modulator therapy restored the reabsorption of aminoglycoside in the proximal tubule of the kidneys, a process that is primarily deficient in patients with cystic fibrosis, thus exacerbating the toxicity of these molecules.